Experimental, analytical and numerical analyses of constant and variable amplitude loadings in the very high cycle fatigue regime. (December 2017) - Stäcker, Carsten; Sander, Manuela
Highlights: VHCF tests at constant and variable amplitudes and different R -ratios are presented. It could be shown that the mean stress effect is influenced in VHCF regime. Variable amplitude loading tests are shifted to higher lifetimes and arrest marks are created. Geometry factor solutions are determined numerically and analytically. Crack propagation simulations at different R -ratios in VHCF regime are performed. Abstract: Mechanical components often exceed a very high number of cycles in their fatigue life. Within the very high cycle fatigue (VHCF) regime, different damage mechanisms occur and the conventional fatigue limit is not valid any more, which has to be considered in a safety–relevant design. Especially in reference to operation loads or variable amplitude loading insufficient knowledge exists. Therefore, within the scope of this paper, the cumulative frequency distributions Felix/28 and WISPER are applied by blocks on a high strength steel by means of an ultrasonic fatigue testing system. The results are compared to those of constant amplitude loading at different stress ratios. Due to the variable amplitude loadings arrest marks are produced within the fish–eye surrounding the inclusion. The sizes and the area, where arrest marks are observable, as well as the spacings between the arrest marks are influenced by the different load sequences. By counting and measuring the arrest marks an average crack growth rate for the crack propagation within the fish eye can be calculated. For further studies a three–dimensional finite element model is created to work out the stress distribution surrounding internal inclusions or cavities and to compare the obtained stress intensity factors of a circumferential crack initiating at the imperfection with analytical solutions. Because VHCF failure is highly dependent on the type of the imperfection and also on the interaction to the surrounding matrix, the stiffness of the inclusion as well as the contact formulation between the matrix and the inclusion in the finite element model are modified. Finally, three–dimensional crack propagation simulations are performed to investigate the influence of crack closure behaviour and the mean stresses.